Public Sector Management in Crisis Contexts: Digital Service Adaptation and Informal Governance - Thein Ye Paing; Sein Aung Tun (Asian Digital Governance Problems, 2025)
Purpose: This study examines how public sector management adapted to prolonged crises through digital service adaptation and informal governance in Myanmar following the COVID-19 pandemic and the 2021 military coup. It aims to explain how these adaptive mechanisms interacted to sustain public service delivery and to develop a conceptual model of crisis governance for institutionally fragile contexts. Subjects and Methods: This research employed an interpretive qualitative case study design using multiple documentary evidence and digital observation. Data were collected from government regulations, institutional reports, humanitarian publications, international organization reports, academic literature, and publicly accessible digital platforms. The data were analyzed through thematic analysis integrated with process tracing to identify the sequential mechanisms underlying governance transformation. Results: The findings reveal that institutional disruption functioned as the primary catalyst for governance transformation, accelerating digital service adaptation and stimulating the emergence of informal governance. Digital technologies evolved beyond administrative tools into mechanisms supporting communication and collaboration, while community organizations compensated for weakened state capacity through flexible and trust-based service delivery. The interaction of these adaptive mechanisms gradually produced a hybrid governance model that strengthened public service continuity despite prolonged institutional instability. Conclusions: This study contributes a conceptual framework integrating institutional disruption, digital adaptation, informal governance, and hybrid governance. The findings highlight that governance resilience depends on adaptive institutional collaboration and inclusive digital ecosystems rather than conventional bureaucratic capacity alone, providing practical implications for crisis governance in fragile institutional settings.